mage of Tamerlane in the Tale of Temir Aksak - Lyapin D.A. (Золотоордынское обозрение)
Research objectives: The author investigates the evolution of the image of Tamerlane (Temir-Aksak) in the Russian chronicles of the fifteenth and sixteenth centuries to understand the specifics of his depiction in different chronicle texts. The author considers it important to analyze the dependence of the image of Tamerlane on the political situation in Russia. Research materials: Three important Russian chronicles of the fifteenth and sixteenth centuries: the Moscow chronicle dating from the end of fifteenth century, the Typographical chronicle, and the Nikon chronicle. In addition, sources of oral origin are investigated – particularly legends. Results and novelty of the research: In the original version (the Moscow collection of the late fifteenth century) of the Tale of Temir Aksak, his image had religious significance and was important for demonstrating the religious idea of God’s intercession on behalf of the Orthodox people. In this text, Tamerlane was presented as a very proud and vicious king who wanted to destroy Orthodoxy. Tamerlane was at war with the religion of the Russians, threatening the Russian Orthodox faith. In the second version of the Tale, found in the Typographic Chronicle, the formidable conqueror is presented as an insidious robber who decided to attack the sacred borders of the Moscow principality. The realization of this idea required an appeal to a Biblical theme. As a result, the plot was based on the story of the invasion of Israel by the Assyrian emperor, Sennacherib. At the same time, the editor of the second version refused to recognize Tamerlane as an authentic emperor. The third version of the Tale, found in the Nikon Chronicle, reflected a new perspective on the events of 1395. To strengthen the motive of divine intercession for Moscow, the author turned Temir Aksak into a real tsar, a formidable conqueror, and a very proud ruler. He decided to conquer the possessions of the Moscow prince though nobody, even the best commander, ought to be permitted to invade the domains of the pious sovereign. For the first time ever, this article shows the evolution of Temir Aksak’s image. The author demonstrates the relationship between its editing and the political situation in Russia. In the sixteenth century, when the Nikon Chronicle was compiled, it was important that Tamerlane was a strong king and a famous commander. But after the decision of the prince Vasily I of Moscow to bring the icon of the Mother of God there, we see God putting the conqueror to flight. Moscow’s prince is the exclusive ruler chosen by God.